E-learning en la enseñanza-aprendizaje de Ciencias Naturales en tercer grado de EGB en la Unidad Educativa Fiscomisional San Francisco de Asís - Romero Labanda, Betty Yadira (2022)
Technology is constantly changing, favoring the development of society, therefore it is necessary to implement E-learning in the educational field in the teaching-learning process through which the student can access various sources of information for the construction of their knowledge. The general objective of this research was to determine the influence of E-learning in teaching-learning in Natural Sciences in third-grade students of Basic Education of the San Francisco de Asís Educational Unit. The methodological approach applied in this research was a mixed approach, that is, qualitative, quantitative, and its design is field research, in which 69 students and 2 third-grade teachers of the subject of Natural Sciences participated. In this investigative process, the scientific, descriptive, inductive, deductive and analytical methods were extracted, in addition the interview directed to the teachers was applied as techniques and within the instruments the questionnaire directed to the students. The results obtained were that the students would like to receive Natural Science classes virtually since the teaching-learning process of this subject seems interesting to them and they can interact in real time with the teacher and classmates, thus promoting cooperative work. Therefore, it is concluded that in the teaching-learning process, scientific skills must be enhanced in which the students learn to manage and make good use of technology, becoming aware that through the use of various digital platforms to consult various topics of interest will increase their knowledge and in turn will participate more actively either in a group or individually, inside and outside the educational community. Keywords: Technology, virtual, digital platforms, teaching-learning, E-learning